Talent identification and recruitment in youth soccer: Recruiter`s perceptions of the key attributes for player recruitment - Larkin, P.; O`Connor, D. (PLOS ONE, 2017)
Using the modified Delphi method, we aimed to understand the attributes youth coaches and recruiters perceive as important when identifying skilled youth performance at the entry level of representative soccer in Australia (i.e., Under 13 years). Furthermore, we also aimed to describe the current methods youth coaches and recruiters use to assess and identify these attributes in youth players. Australian regional youth technical directors and coaches (n = 20) completed a three stage process, including an initial interview and two subsequent questionnaires, whereby attributes and qualities associated with talent identification were rated and justified according to the importance for youth player performance and talent identification. Results indicate a hierarchy of attributes recruiters perceive as important for Under 13 soccer performance, including technical (i.e., first touch, striking the ball, one-versus-one ability, and technical ability under pressure), tactical (i.e., decision-making ability) and psychological attributes (i.e., coachability and positive attitude). In addition, the findings indicated attributes and qualities not emphasised within the talent identification process including, physiological, anthropometrical, sociological and several psychological attributes. It is suggested talent recruiters apply a holistic multidisciplinary approach to talent identification, with the current findings potentially providing initial evidence to suggest recruiters do consider numerous attributes when selecting and identifying youth players.